Identifying solid luminogens through gold-catalysed intramolecular hydroarylation of alkynes - Shaikh, Aslam C.; Shalini, S.; Vaidhyanathan, Ramanathan; Mane, Manoj V.; Barui, Ayan Kumar; Patra, Chitta Ranjan; Venkatesh, Yeduru; Bangal, Prakriti Ranjan; Patil, Nitin T. (European Journal of Organic Chemistry, 2015)
The identification of a new class of luminogens based on pyrrolo-quinoxaline embedded coumarin (PQC) structures is reported. The reaction relies on the gold-catalyzed hydroarylation reaction of appropriately substituted aryl alkynoates that produces molecules that exhibit solvatochromism and aggregation-induced emission enhancement (AIEE) phenomena. The application of PQCs for live cell imaging has also been demonstrated.
Keywords: Cell imaging; Dyes/pigments; fluorescence; Gold; Luminescence; Solvatochromism

Intramolecular ipso-arylative cyclization of aryl-alkynoates and N-arylpropiolamides with aryldiazonium salts through merged gold/visible light photoredox catalysis - Bansode, Avinash H.; Shaikh, Samir R.; Gonnade, Rajesh G.; Patil, Nitin T. (Chemical Communications, 2017)
A visible-light-promoted merged gold/photoredox catalyzed ipsoarylative cyclization has been reported. For instance, the reaction of aryl-alkynoates and N-arylpropiolamides with aryldiazonium salts in the presence of catalytic amounts of [(4-OCH3)C6H4](3)PAuCl and Ru(bpy)(3)(PF6)(2) under irradiation using a 32WCFL bulb gave arylated spirocarbocycles in moderate to good yields.

Ionic pyridinium-oxazole dyads: design, synthesis, and application in mitochondrial imaging - Shaikh, Aslam C.; Varma, Mokshada E.; Mule, Ravindra D.; Banerjee, Somsuvra; Kulkarni, Prasad P.; Patil, Nitin T. (Journal of Organic Chemistry, 2019)
We recently developed an oxidative intramolecular 1,2-amino-oxygenation reaction, combining gold(I)/gold(III) catalysis, for accessing structurally unique ionic pyridinium-oxazole dyads (PODs) with tunable emission wavelengths. On further investigation, these fluorophores turned out to be potential biomarkers; in particular, the one containing -NMe2 functionality (NMe2-POD) was highly selective for mitochondrial imaging. Of note, because of mitochondria's involvement in early-stage apoptosis and degenerative conditions, tracking the dynamics of mitochondrial morphology with such imaging technology has attracted much interest. Along this line, we wanted to build a library of such PODs which are potential mitochondria trackers. However, Au/Selecfluor, our first-generation catalyst system, suffers from undesired fluorination of electronically rich PODs resulting in an inseparable mixture (1:1) of the PODs and their fluorinated derivatives. In our attempt to search for a better alternative to circumvent this issue, we developed a second-generation approach for the synthesis of PODs by employing Cu(II)/PhI(OAC)(2)-mediated oxidative 1,2-amino-oxygenation of alkynes. Thes newly synthesized PODs exhibit tunable emissions as well as excellent quantum efficiency up to 0.96. Further, this powerful process gives rapid access to a library of NMe2-PODs which are potential mitochondrial imaging agents. Out of the library, the randomly chosen POD-3g was studied for cell-imaging experiments which showed high mitochondrial specificity, superior photostability, and appreciable tolerance to microenvironment changes with respect to commercially available MitoTracker green.

Interplay of anion-pi(+) and pi(+)-pi(+) interactions in novel pyrido[2,1-a]isoquinolinium-based aiegens - substituent- and counterion-dependent fluorescence modulation and applications in live cell mitochondrial imaging - Mule, Ravindra D.; Roy, Rupam; Mandal, Koushik; Chopra, Deepak; Dutta, Tanoy; Sancheti, Shashank P.; Shinde, Popat S.; Banerjee, Somsuvra; Lal Koner, Apurba; Bhowal, Rohit; Senthilkumar, Beeran; Patil, Nitin T. (Chemistry-A European Journal, 2022)
Recently, the concept of anion-pi(+) interactions has witnessed unique applications in the field of AIEgen development. In this contribution, we disclose a consolidated study of a library of N-doped ionic AIEgens accessed through silver-mediated cyclization of pyridino-alkynes. A thorough photophysical, computational and crystallographic study has been conducted to rationalize the observed substituent- and counterion-dependent fluorescence properties of these luminogens. We further elucidate the prominent role of anion-pi(+) interactions, pi(+)-pi(+) interactions and other non-covalent interactions, in inhibiting the undesired ACQ effect. Finally, we have also demonstrated the application of selected AIEgens for imaging of mitochondria in live cells.
Keywords: 1-a]isoquinolinium; AIEgens; anion-pi(+); crystal structure; mitochondrial imaging; pyrido[2